(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
It is known that those who will realize the goals of the society in the future are young people, that is, tomorrow’s specialists, current students. Therefore, the future of the society depends to a large extent on their intellectual and moral maturity. Problems of forming the activity of independent thinking, methods of getting out of the set problem. If criticality in the learner’s thinking is rationally, fairly, and effectively implemented, it becomes an important intellectual and moral quality (character) for the individual.